2016
DOI: 10.1002/2015ja022216
|View full text |Cite
|
Sign up to set email alerts
|

From Alfvén waves to kinetic Alfvén waves in an inhomogeneous equilibrium structure

Abstract: Kinetic Alfvén waves are believed to primary form fluctuations in a hydromagnetic turbulence at scales of the order of the ion inertial length. We study a model where an initial Alfvén wave propagates inside an equilibrium structure which is inhomogeneous in the direction perpendicular to the equilibrium magnetic field. In a previous paper this situation has been considered in a particular configuration where the initial wave vector is parallel to the magnetic field and the wave is polarized perpendicular to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 82 publications
(93 reference statements)
3
34
0
Order By: Relevance
“…Many observations at ion and sub-ion scales, specifically, suggest that turbulent fluctuations exhibit properties mainly typical of kinetic Alfvén waves (KAWs) (Leamon et al, 1998;Sahraoui et al, 2009;Podesta and TenBarge, 2012;Salem et al, 2012;Chen et al, 2013;Chen, 2016;Kiyani et al, 2013;Lacombe et al, 2017). The emergence of KAW-like fluctuations in kinetic turbulence has been also supported by means of a large number of theoretical and numerical works (e.g., Hollweg, 1999;Stawicki et al, 2001;Gary and Nishimura, 2004;Howes et al, 2008a;Gary and Smith, 2009;Sahraoui et al, 2012;TenBarge et al, 2012;Vásconez et al, 2014Vásconez et al, , 2015Franci et al, 2015;Cerri et al, 2016;Pucci et al, 2016;Zhao et al, 2016;Valentini et al, 2017;Grošelj et al, 2019). Some of these studies rely on the so-called spectral field ratios, which provide a measure of the wave-like polarization properties of the turbulent fluctuations, as compared to what linear theory predicts (see, e.g., Boldyrev et al, 2013, and Sec.…”
Section: Introductionmentioning
confidence: 97%
“…Many observations at ion and sub-ion scales, specifically, suggest that turbulent fluctuations exhibit properties mainly typical of kinetic Alfvén waves (KAWs) (Leamon et al, 1998;Sahraoui et al, 2009;Podesta and TenBarge, 2012;Salem et al, 2012;Chen et al, 2013;Chen, 2016;Kiyani et al, 2013;Lacombe et al, 2017). The emergence of KAW-like fluctuations in kinetic turbulence has been also supported by means of a large number of theoretical and numerical works (e.g., Hollweg, 1999;Stawicki et al, 2001;Gary and Nishimura, 2004;Howes et al, 2008a;Gary and Smith, 2009;Sahraoui et al, 2012;TenBarge et al, 2012;Vásconez et al, 2014Vásconez et al, , 2015Franci et al, 2015;Cerri et al, 2016;Pucci et al, 2016;Zhao et al, 2016;Valentini et al, 2017;Grošelj et al, 2019). Some of these studies rely on the so-called spectral field ratios, which provide a measure of the wave-like polarization properties of the turbulent fluctuations, as compared to what linear theory predicts (see, e.g., Boldyrev et al, 2013, and Sec.…”
Section: Introductionmentioning
confidence: 97%
“…Recent analysis has revealed that the temperature and energized particles are enhanced in the proximity of current sheets [30][31][32][33][34] or of locations of concentration of tur-bulent energy [27,35]. The local, fine details of the energy transfer process in the turbulent cascade may therefore play a fundamental role in the activation of those plasma kinetic processes that are believed to be responsible for energy conversion, usually (and loosely) referred to as dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…These intervals were chosen as there is no connection to the foreshock and the Cluster spacecraft configuration has inter-spacecraft distances of ∼ 200 km in a nearly regular tetrahedral configuration with low values of the planarity and elongation parameters (Robert et al, 1998). This allows the investigation of the proton kinetic scales without bias due to inhomogeneous spatial sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Several different schemes have been employed including magnetohydrodynamic (MHD) at large scales (e.g. Verdini and Grappin, 2015;Mallet et al, 2016;Pezzi et al, 2017a;Pezzi et al, 2017b), Hall MHD for scales at the transition between proton and electron scales (Pucci et al, 2016;Pezzi et al, 2017a;Pezzi et al, 2017b), hybrid Vlasov (e.g. Perrone et al, 2013;Franci et al, 2015a, b;Valentini et al, 2016;Cerri et al, 2016Cerri et al, , 2017Pezzi et al, 2017a;Pezzi et al, 2017b) or hybrid particle in cell for proton kinetic scales, finally full particle in cell descriptions can be used to investigate sub-ion scales (Camporeale and Burgess, 2011;Haynes et al, 2014; see also the review by Servidio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%